2005
DOI: 10.1074/jbc.m411918200
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Malate/Lactate Dehydrogenase from Pseudomonas putida Is an NADPH-dependent Δ1-Piperideine-2-carboxylate/Δ1-Pyrroline-2-carboxylate Reductase Involved in the Catabolism of d-Lysine and d-Proline

Abstract: A Pseudomonas putida ATCC12633 gene, dpkA, encoding a putative protein annotated as malate/L-lactate dehydrogenase in various sequence data bases was disrupted by homologous recombination. The resultant dpkA ؊ mutant was deprived of the ability to use D-lysine and also D-proline as a sole carbon source. The dpkA gene was cloned and overexpressed in Escherichia coli, and the gene product was characterized. The enzyme showed neither malate dehydrogenase nor lactate dehydrogenase activity but catalyzed the NADPH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 35 publications
(38 reference statements)
2
63
0
Order By: Relevance
“…On the contrary, the dpkA mutant lost the ability to grow on D-Pro as the sole nitrogen source, and this growth defect was complemented by the dkpA clone. This result was consistent with the reported functions of dkpA in P. putida (Muramatsu et al, 2005).…”
Section: Growth Phenotypessupporting
confidence: 83%
See 1 more Smart Citation
“…On the contrary, the dpkA mutant lost the ability to grow on D-Pro as the sole nitrogen source, and this growth defect was complemented by the dkpA clone. This result was consistent with the reported functions of dkpA in P. putida (Muramatsu et al, 2005).…”
Section: Growth Phenotypessupporting
confidence: 83%
“…The PA1255 gene following lhpPHMNO codes for a putative amino acid racemase, and was designated as lhpK here in this study. The peptide encoded by the stand-alone PA1252 gene exhibited moderate sequence similarity to DpkA of P. putida KT2440 that has been reported as an NADP-dependent D1-piperideine-2-carboxylate/D1-pyrroline-2-carboxylate reductase in the catabolism of D-lysine and D-proline (Muramatsu et al, 2005). Also listed in the table were PA1261 (lhpR) and PA1269 encoding two transcriptional regulators, although they were not induced by L-Hyp or D-Hyp.…”
Section: Dna Microarrays Analysismentioning
confidence: 99%
“…One missing link in the converged pathway is the enzyme converting D9-piperidine-2-carboxylate to L-Pip. One potential candidate for this enzyme was encoded by PA1252, based on its sequence similarity to DpkA (PP3591) of P. putida KT2440 that has been previously shown to catalyse this reaction in D-Lys and D-Pro catabolism (Muramatsu et al, 2005;Revelles et al, 2005). From the results of transcriptome analysis (Table 3), the PA1252 gene was found not to be inducible by L-Lys, D-Lys or L-Pip.…”
Section: Induction Of the Amaab Promotermentioning
confidence: 97%
“…1) has been proposed to degrade D-Lys to 2-aminoadipate, which is then further degraded to a-ketoglutarate to enter the Krebs cycle. Several genes encoding enzymes of this proposed pathway in P. putida KT2440 have been identified, including PP3590 for D-Lys transaminase, PP3596 for D-Lys dehydrogenase, dpkA for D1-piperideine-2-carboxylate reductase (Muramatsu et al, 2005;Revelles et al, 2005Revelles et al, , 2007, and amaB and amaA in conversion of pipecolate to 2-aminoadipate (Revelles et al, 2005). P. aeruginosa does not possess the lysine racemase; however, L-Lys catabolism can potentially be connected to the D-Lys pathway via an arginine-pyruvate transaminase AruH (Chou et al, 2010;Yang & Lu, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…These two enzymes and their homologs have thus been annotated as new MDH/LDHs different from the conventional MDH/LDH. Recent biochemical and genetic studies have revealed that some of the gene products homologous to proteins belonging to the new MDH/LDH family catalyze reactions other than those involved in MDH or LDH activity, as exemplified by L-sulfolactate dehydrogenase (SLDH) (5), ureidoglycolate dehydrogenase (UGDH) (6), 2,3-diketo-L-gulonate reductase (YiaK) (7), and ⌬ 1 -piperideine-2-carboxylate (Pip2C)/ ⌬ 1 -pyrroline-2-carboxylate (Pyr2C) reductase (8). ThenewMDH/LDHfamilyhasnowbeenextendedtothenewNAD(P)Hdependent oxidoreductase family which contains proteins homologous to, but different in activities from, the new family of MDH/LDH proteins (5,9).…”
mentioning
confidence: 99%